Initial clinical experience with BRAFV600E mutation analysis of core‐needle biopsy specimens from thyroid nodules. (27th August 2015) - Choi, Sang Hyun; Baek, Jung Hwan; Lee, Jeong Hyun; Choi, Young Jun; Ha, Eun Ju; Song, Dong Eun; Kim, Jae Kyun; Chung, Ki‐Wook; Kim, Tae Yong; Kim, Won Bae; Shong, Young Kee
Summary: Objective: The accurate diagnosis of thyroid nodules is important for making management decisions. The purpose of this study was to evaluate the feasibility of core‐needle biopsy with BRAF V600E mutation analysis (CNB + BRAF V600E ) and to compare the clinical usefulness of CNB + BRAF V600E and fine‐needle aspiration with BRAF V600E mutation analysis (FNA + BRAF V600E ) in the diagnosis of thyroid malignancy. Design, patients and measurements: The results of BRAF V600E mutation analyses of 820 nodules from 820 patients (153 men, 667 women; mean age, 51·1 years), who underwent CNB + BRAF V600E ( n = 256) or FNA + BRAF V600E ( n = 564) between January 2011 and March 2012 were retrospectively evaluated. The feasibility of CNB + BRAF V600E was assessed by comparing its rate of detection of BRAF V600E mutations and positive predictive value with those of FNA + BRAF V600E . The clinical usefulness of CNB + BRAF V600E was determined by comparing rates of inconclusive results, the additional value of BRAF V600E mutation analysis, diagnostic surgery and diagnostic performance with those of FNA + BRAF V600E . Results: CNB + BRAF V600E and FNA + BRAF V600E had similar rates of BRAF V600E mutation detection (66·3% vs 64·4%, P = 0·883) and positive predictive value (100·0% vs 96·6%, P = 0·135). CNB + BRAF V600E had a significantly higher diagnostic accuracy rate (95·7% vs 85·9%, P < 0·001), and significantly lower rates of inconclusive results (8·2% vs 51·8%, P < 0·001), and diagnostic surgery (8·9% vs 22·3%, P = 0·006), than FNA + BRAF V600E . Conclusions: The greater diagnostic performance of CNB + BRAF V600E and its lower rate of inconclusive results than FNA + BRAF V600E suggest that CNB + BRAF V600E can reduce rates of preventable diagnostic surgery.